Conceptions of good teaching in professors’ narratives: pre-service EFL teaching education (Praxis Educativa, 2012)
The research project "Good Teaching Practices and Teacher Education Contributions Towards a New Pedagogical Agenda" studies good teaching in the EFL Teacher Education Program at the School of Humanities. Mar del Plata State University, Argentina The investigation proceeds within the framework of the new agenda for didactics It began by identifying good practices through a semi-open questionnaire administered to a selected sample of good senior students in the Program Recorded instructors were interviewed by means of a semi-flexible script emphasizing their narrative perspectives This paper summarizes a comparative analysis of conceptions of good teaching registered for two professors. The interpretation of these stories aims at generating categories to publicly and theoretically signify their private teaching experiences. This process allows for the exploration of some of the complexities concerning pre-service EFL teaching education.
Keywords: Teacher Education; EFLT Didactics; good teaching practices